Development of a Website-Based BUBUMA Digital Learning Media to Enhance Elementary School Students’ Conceptual Understanding - Syntia Eka Putri Setioyuliani; Ipin Aripin (Lembaga Penelitian dan Pengembangan Sumberdaya Wilayah (elrispeswil), 2026)
The low level of elementary school students’ conceptual understanding of abstract topics such as Earth and Space exploration highlights the need for learning media that can present concepts in a concrete, interactive, and accessible manner. This study aims to develop, validate, and evaluate the effectiveness of a website-based BUBUMA digital learning media in improving sixth-grade students’ conceptual understanding at SDN Nongkosawit 02. This research employed a Research and Development (R&D) approach using the ADDIE model, consisting of Analyze, Design, Development, Implementation, and Evaluation stages. Product feasibility was assessed through expert validation involving media, content, and language experts, while effectiveness was tested using a one-group pretest-posttest design involving 20 students. Data were analyzed using descriptive statistics, paired sample t-test, and N-Gain analysis. The results indicate that the BUBUMA website-based media is highly feasible. Furthermore, there was a significant improvement in students’ conceptual understanding, as reflected by the increase in mean scores from 56.00 to 82.50 (p = 0.001) with an N-Gain of 0.59 (moderate category). These findings suggest that website-based digital media is effective in supporting the learning of abstract concepts in elementary education.